Breastfeeding to reduce postpartum weight retention - Padmawati, Rinela; Dasuki, Djaswadi; Sudargo, Toto (International Journal Of Community Medicine And Public Health, 2016)
Background: Postpartum weight retention is regarded as a major public health problem because of its contribution to the incidence of obesity. Evidence regarding the effect of breastfeeding on postpartum weight retention reduction is still controversial and limited. In 3 to 6 months of postpartum, not all women will be losing weight, so that efforts are required to reduce postpartum weight retention. This study to determine the effect of breastfeeding on postpartum weight retention. Methods: This was an observational study with a prospective cohort design. The duration of this study for three months after childbirth. The study population was all lactating mothers in Cirebon Municipality. Samples were taken with a purposive sampling technique in Cirebon with a sample size of 80 people. The data used were primary and secondary data and the instrument used were a questionnaire and adult weight scale. Data were processed using univariate analysis, bivariate analysis with ANOVA and t-test, and multivariate analysis with linear regression. Results: Postpartum weight retention was much more in partially breastfeeding mothers compared with those who breastfed fully (p=0.0021). Breastfeeding can reduce postpartum weight retention at 2.57kg. Breastfeeding after being controlled with food intake, weight gain during pregnancy, and physical activity showed a significant association with postpartum weight retention and can reduce postpartum weight retention at 2.26kg (p =0.000). Conclusions: Breastfeeding could reduce postpartum weight retention. Weight gain during pregnancy, food intake, and physical activity might influence postpartum weight retention.